Pendampingan Penyusunan Rencana Karier dan Pembuatan Portofolio Digital untuk Meningkatkan Persiapan Karier Siswa di SMK - Rowiyani Rowiyani; Wellie Sulistijanti; Arista Fitri Diana; Khoerul Soleh; Muhammad Haikal Darmawan (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Vocational school students often face challenges in planning their career paths and presenting their competencies in a structured and digital format. This community service program aims to assist students in preparing career plans and developing digital portfolios that reflect their personal achievements, skills, and aspirations. The activity was conducted in three stages: (1) initial preparation involving coordination with the school and student needs assessment, (2) interactive training on career planning and digital portfolio creation using platforms such as Canva and Google Sites, and (3) feedback sessions where students presented their portfolios and received constructive input. Throughout the program, students were guided on how to reflect their strengths, skills, and future aspirations into a digital format, providing them with a comprehensive tool for job applications or further studies. The results showed a significant increase in students’ understanding of career planning and their ability to independently create well-structured digital portfolios. The majority of participants (78%) completed their digital portfolios, and over 80% were actively engaged during the sessions, demonstrating a high level of enthusiasm and commitment. This program highlights the effectiveness of a participatory and practice-based approach in enhancing students' career readiness and equipping them with essential tools for the modern job market. The students’ improved ability to showcase their competencies in a digital format also supports the evolving needs of employers in the digital age. Future programs are recommended to include advanced modules on digital personal branding, interview preparation, and networking skills to further support vocational students in successfully entering the workforce or continuing their education.